Abans del 1914: Què pensaven les militàncies obreres i republicanes? - Pere Gabriel (Catalonia)
The article presents an overview of the political cultures active within the labour movement and the Catalan popular sectors throughout the nineteenth century. I give a diachronic example based on the meaning and interpretations of what was meant by socialism throughout the nineteenth century. However, a long-term perspective does not mean to ignore the chronology, and I devote a section to the working-class and popular militancy of the eight hundred years before republicanism and Catalanism. The article also reflects extensively on Catalan trade unionism throughout the nineteenth century.